Disability Status Attenuates Treatment Effects in an Intensive Outpatient Program for PTSD. (25th January 2021) - Hoyt, Tim; Shumaker, Brianna E Staley
ABSTRACT: Introduction: The utilization of intensive outpatient programs for the treatment of military-related post-traumatic stress disorder (PTSD) has increased through initiatives both inside and outside the military health care system. However, research in veteran populations suggest that patients concurrently undergoing disability evaluation may not respond well to such interventions. This study evaluates the relationship between disability separation and endorsement of PTSD symptoms during treatment at an intensive outpatient program. Methods: Patients in this retrospective study were 81 service members enrolled in a half-day, 6-week intensive outpatient program for PTSD. Sixty-seven percent ( n  = 54) were concurrently enrolled in the integrated disability evaluation system and were pending medical separation. Fifty-two percent ( n  = 42) also received a 4-week skills training intervention before beginning PTSD treatment. Patients completed the PTSD Checklist before, during, and after the treatment program as an index of PTSD symptoms. Results: A significant interaction effect was observed in which PTSD symptoms throughout program enrollment differed as a function of enrollment in the integrated disability evaluation system. Patients undergoing disability evaluations did not show significant changes in endorsed PTSD symptoms during program enrollment, whereas significant decreases in PTSD symptoms were observed in patients not undergoing disability evaluations. These effects controlled for lost treatment days as a result of training or other appointments. Conclusions: These results provide preliminary data indicating that participation in disability separation may attenuate the effect of PTSD treatment and endorsement of PTSD symptoms in an intensive outpatient setting.